1. Hu S, Sprintall J, Guan C, et al. Deep-reaching acceleration of global mean ocean circulation over the past two decades. Sci Adv. 2020;6(6):eaax7727. - Shijian Hu; Wenju Cai (TheScienceBreaker, 2020)
The consequence of enhanced energy metabolism for health and life span of organisms is a fundamental yet controversially discussed issue of life and aging among others because of the fact that increasing energy metabolism often entails the risk of oxidative damage. To resolve this paradox, we introduce the bacterial-derived lipoic acid protein ligase A (LplA) as an orthogonal and defined molecular tool to enhance energy metabolism and at the same time to foster a low oxidative stress environment. Investigations in Caenorhabditis elegans (C. elegans) and mouse models demonstrate that LplA expression significantly enhances energy metabolism and health across the life span, without compromising maximum longevity. Our work not only transcends the long-standing paradox between energy metabolism and health life span but also provides a hereto unreported strategy to intervene in human aging.